Anticancer Potential and Mechanism of Action of Mango Ginger ( Roxb.) Supercritical CO Extract in Human Glioblastoma Cells - Cheppail Ramachandran PhD, MBA; Ivonne V. Lollett BS; Enrique Escalon MD; Karl-Werner Quirin PhD; Steven J. Melnick PhD, MD (SAGE Publishing, 2015)
Mango ginger ( Curcuma amada Roxb.) is among the less-investigated species of Curcuma for anticancer properties. We have investigated the anticancer potential and the mechanism of action of a supercritical CO 2 extract of mango ginger (CA) in the U-87MG human glioblastoma cell line. CA demonstrated higher cytotoxicity than temozolomide, etoposide, curcumin, and turmeric force with IC 50 , IC 75 , and IC 90 values of 4.92 μg/mL, 12.87 μg/mL, and 21.30 μg/mL, respectively. Inhibitory concentration values of CA for normal embryonic mouse hypothalamus cell line (mHypoE-N1) is significantly higher than glioblastoma cell line, indicating the specificity of CA against brain tumor cells. CompuSyn analysis indicates that CA acts synergistically with temozolomide and etoposide for the cytotoxicity with combination index values of <1. CA treatment also induces apoptosis in glioblastoma cells in a dose-dependent manner and downregulates genes associated with apoptosis, cell proliferation, telomerase activity, oncogenesis, and drug resistance in glioblastoma cells.